Xanthomicrol suppresses human hepatocellular carcinoma cells migration and invasion ability via Μu-opioid receptor. (6th August 2021) - Lin, Zi-Zhong; Bo, Nie; Fan, Yu-Chun; Wu, Yan-Ting; Yao, Hong-Liang; Chen, Su; Yu, Hui-Fan; Jiang, Li-He
Abstract: Background: Xanthomicrol is one of the methoxylated flavones and a promising cancer chemopreventive agent, but its anti-migration and anti-invasion ability on human hepatocellular carcinoma (HCC) remains unknown. Objectives: This study aims to explore Xanthomicrol's effects on migration and invasion ability of the human HCC Huh7 cell line. Methods: Viability of Huh7 cells was measured by cell counting kit-8 (CCK8) assay. Cell apoptosis was assayed with flow cytometry analysis. The ability of migration and invasion of Huh7 cells was then detected through Transwell assays. Epithelial–mesenchymal transition (EMT)-related proteins were also detected through Western blot. Key findings: Xanthomicrol inhibits the migration and invasion of Huh7 cells. The overexpression of Μu-opioid receptor (MOR) increases Huh7 cells' proliferation and enhances migration and invasion ability, while xanthomicrol treatment decreases the expression of MOR. Moreover, xanthomicrol can reverse migration, invasion and EMT-related protein expression by overexpressed MOR. Conclusions: These results suggest that xanthomicrol is a potential MOR antagonist, and it possesses potent anti-migration and anti-invasion ability on Huh7 cells.